ChemInform Abstract: A Facile Approach for the Asymmetric Synthesis of Oxindoles with a 3‐Sulfenyl‐Substituted Quaternary Stereocenter. Issue 10 (11th March 2014) - Dou, Xiaowei; Zhou, Bo; Yao, Weijun; Zhong, Fangrui; Jiang, Chunhui; Lu, Yixin
Abstract Michael addition of various sulfenyloxindoles to nitroolefins proceeds stereoselectively using a quinine catalyst bearing a silyl‐threonine moiety to give oxindoles with a 3‐sulfenyl‐substituted quaternary center in excellent yields and with high diastereoselectivities and excellent enantioselectivities.